PLANTATION PARTNERSHIP DEVELOPMENT PATTERNS: AGRICULTURAL EXTENSION INSTITUTES' ROLES AND LIMITS - Lili Dahliani; Samuel Karim (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2022)
Agricultural extension institutions serve as communication hubs that facilitate the exchange of information between farmers, the government, and institutional partners of farmer groups. Farmers must receive clear and practical information from extension institutions. This study aims to ascertain the role and function of extension institutions in promoting agricultural development in the plantation sector in Bogor. Additionally, it intends to identify extension workers' challenges and evaluate their contribution to agricultural development. The study employed a qualitative approach, utilizing data-gathering methods like observation and interviews. The participants included farmers, farming instructors, and members of the extension sector from the Bogor Agricultural Institute. The research findings elucidate the significance and function of plantation agricultural extension institutions in rural development, encompassing services, communication centers, and institutional development centers. The potential of partnerships and the role of extension institutions, including program planning and preparation, information provision and dissemination, human resource development, administrative structuring, and evaluation activities, have yet to be fully utilized. There is a demand for more agricultural teachers specializing in plantation crops and improved training opportunities for these instructors. Additionally, there should be a clear policy to facilitate the transition of plantation instructors to become instructors for food crops. Agricultural (plantation) development contributes to economic growth, community welfare, and enhanced plantation output outcomes. There is an expectation that the decrease in production output of various commodities, such as cloves, rubber, cocoa, and coffee, can be enhanced by augmenting the knowledge and expertise of farmers and their families while transforming their traditional farming practices into more modern ones.